THE INFLUENCE OF INVENTORY TURNOVER TO RETURN ONINVESTMENT (ROI) AT CV. ARMICO - Riza Anggraeni, - (2010)
CV.Armico is one of the publishers who' are located in Bandung. In this research to know the performance CV.Armico one of them by using the profitability ratio analysis. One of the ratio of profitability to measure the level of Return on Investment (ROI). In this case, Return on Investment (ROI) that occurred in CV.Armico have any meaning that is also very important as the analysis of financial reports that are complete (comprehensive). But in an increasingly tight competition, the decline in ROI is a problem that may occur for each company, such as that experienced by CV Armico years in the period 1998-2007. The goal in this research is to know how to change a stock of inventory, to know how the Return on Investment (ROI), and know how the influence of inventory turn over to ROI. In this research the author uses the method verifikatif. Basically verifikatif method is a method used to test the truth of a hypothetical that was conducted through the collection of data in the field. To analyze the data using the author product moment correlation coefficients used to know the degree of relationship between variables X (inventory turnover) with variables Y (ROI). The data collection technique used was the assessment document with a hypothetical research is formulated level inventory turn over have a positive influence on ROI. After the calculation and analysis of data by using the Product Moment correlation coefficients, the results obtained is 0.98. This means that the level inventory turn over have a relationship with ROI-positive and have a very strong relationship. To find out how big the influence of rotation between the level inventory turn over to be ROI, then the coefficients determination should be calculated after the calculation of the value of 96.04%. This shows that the level inventory turn over has rotation of 96.04% of the ROI, while the remaining 3.96% is influenced by other factors.